Respon Mahasiswa Terhadap Penggunaan Video Pembelajaran Berbasis Canva Design pada Mata Kuliah Fisika Listrik Statis - Astuti, Siwi Puji (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2022)
The aim of the study was to determine the effectiveness of using Canva's learning videos on static electricity. At this stage of research, the learning media has been created by researchers and has been validated by material experts and media experts, with the results being feasible to be used as static electricity learning media. So from these results the researchers will test the effectiveness of users, which are tested on Informatics Engineering students at Indraprasta University. The research method used is the survey method. This survey method uses data collection techniques using questionnaires/questionnaires. The questionnaire method is used to determine a product by testing the validation of the product we have developed. In previous studies, media validation tests have been carried out by material experts and media experts. Furthermore, a feasibility test is carried out which is tested on students. The instrument used is a questionnaire from student responses. And the research sample is the Informatics Engineering student of class R45 as many as 43 students and R46 as many as 42 students, so that the total research sample is 85 students. From the results of the feasibility test of this learning media, students stated that they agreed to use physics learning media using Canva in static electricity physics courses conducted online. This learning media using Canva Design makes it easy for teachers to deliver learning materials in online conditions like today.